DE LA CAJA DE HERRAMIENTAS A LA POÉTICA DEL PALIMPSESTO: EL CINE EN EL HACER DE LAS ARTES EN MÉXICO - Dr. Miguel ERRAZU,Dra. María Luisa ORTEGA (Fonseca, Journal of Communication, 2023)
This paper sets out an analysis of the varying forms in which cinema has intervened in the practices and imaginaries of contemporary art in Mexico, from the 1930s to the second decade of the XX’s Century. First, we draw a theoretical review of intermediality and other useful methodological frameworks for the study of the interactions between cinema and the other arts